Biomedical Optics 2014 2014
DOI: 10.1364/biomed.2014.bs3a.69
|View full text |Cite
|
Sign up to set email alerts
|

Fully motorized optical-resolution photoacoustic microscopy

Abstract: We have developed fully motorized optical-resolution photoacoustic microscopy (OR-PAM), which integrates five complementary scanning modes and simultaneously provides a high imaging speed and a wide field of view (FOV) with 2.6 μm lateral resolution. With one-dimensional (1D) motion-mode mechanical scanning, we measured the blood flow through a cross section of a blood vessel in vivo. With two-dimensional (2D) optical scanning at a laser repetition rate of 40 kHz, we achieved a 2 kHz B-scan rate over a range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…In addition, since the focal distance is very critical to obtain the highest resolution imaging, rough tissue surface due to diseased skin in Gli mice might have resulted in the variations in the focal length, which will affect the spot size. As Li et al have shown, a slight difference in height caused by a tumor can make an area appear devoid of vessels and correcting the height of the scanner allows for improved visualization of microvasculature [37]. We will be adapting our system and algorithm to accommodate these types of physiological variations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, since the focal distance is very critical to obtain the highest resolution imaging, rough tissue surface due to diseased skin in Gli mice might have resulted in the variations in the focal length, which will affect the spot size. As Li et al have shown, a slight difference in height caused by a tumor can make an area appear devoid of vessels and correcting the height of the scanner allows for improved visualization of microvasculature [37]. We will be adapting our system and algorithm to accommodate these types of physiological variations.…”
Section: Discussionmentioning
confidence: 99%
“…To boost the speed of PAM while maintaining the slow B-scan rate for the CBF measurement, we adopted the synchronized one-dimensional optical and two-dimensional (2-D) mechanical hybrid scan. 11 As shown in Fig. 2(a), the galvanometer scanner steers the laser spot along the Y-axis within the acoustic focus of the transducer at a round-trip rate of 2.1 kHz as the linear stage mechanically translates the optical-acoustic dual foci along the X-axis at a constant speed of 0.88 mm∕s, during which the laser output is switched between 532 and 558 nm at a 3.3-μs interval to produce dual-wavelength A-line pairs.…”
Section: Scanning Mechanism and Measurement Principlementioning
confidence: 99%
“…For the purpose of measuring the lateral resolution of the system the 10x Olympus objective was used. We verified the resolution by applying the step-edge method [25]. For this method a sharp-edged object is imaged for the experimental quantification of the imaging system resolution.…”
Section: Photoacoustic Biomedical Application Of the All-optical Akinmentioning
confidence: 99%